Imbalance Between Injury and Defense in the COPD Emphysematous Phenotype - Bai, Shuang; Zhao, Li (Frontiers in Medicine, 2021)
Chronic obstructive pulmonary disease (COPD) emphysematous phenotype is characterized by destruction of lung tissue structure. Patients with this phenotype usually show typical emphysema-like changes on chest CT, manifest as higher mortality and poorer prognosis, and are insensitivity to routine pharmacological therapy of COPD. However, the pathogenesis for COPD emphysematous phenotype is still unclear, resulting great difficulties for diagnosis and treatments. Injury and defense imbalance is essential in the progression of many pulmonary diseases. In this review, we focus on the pathogenesis of COPD emphysematous phenotype and discuss pathophysiological processes during disease progression from an injury and defense imbalance perspective.